Comparing Treatment with Nebulized 3% Hypertonic Saline Versus Nebulized 0.9% Saline In Patients With Acute Bronchiolitis: A Double-Blind Randomized Controlled Trial - Uzma Abid; Ayesha Afzal; Nahdia Zaman; Ammara Farooq; Sidrah Yousaf; Sonia Fazal (Journal of Rawalpindi Medical College)
Objective: To establish the therapeutic role of nebulized hypertonic saline solution in the management of acute bronchiolitis in terms of primary and secondary outcomes.